The critical role of miRNAs in modulating PRRSV infection in swine: a review - Yu-Chen Wang; Zhi-Yong Shao; Wei-Xue Yi; Li-Jun Wu; Wei Liu; Xia-Bing Chen; Rui-Ge Cao; Bin He (BMC, 2024)
Abstract Porcine reproductive and respiratory syndrome (PRRS) is a severe threat to pig farming worldwide and contributes to substantial financial losses. Endogenous short RNAs, known as microRNAs (miRNAs), play various roles in controlling viral infections in both human and animals through virus‒host interactions, mediating immune-related gene responses in target cells despite their unknown precise roles in infectious illnesses. Thus, a comprehensive literature search was conducted in EMBASE, PubMed and Web of Science databases to compile this review, focusing on the function, role, and involvement of miRNAs in porcine reproductive and respiratory syndrome virus (PRRSV) infection. In addition to possible exogenous miRNAs such as miR2911 and miR168, our study provides strong evidence demonstrating the important effects of endogenous miRNAs such as miR-181, miR-26, and miR-145 on PRRSV infection, which were also anticipated to bind to certain locations within PRRSV genomes. Our study highlights that miRNAs can serve as a treatment strategy of PRRS and further research is needed to validate their clinical safety and efficacy.